A multi‐ethnic analysis of immune‐related gene expression signatures in patients with ovarian clear cell carcinoma. Issue 3 (1st September 2021) - Heong, Valerie; Tan, Tuan Z; Miwa, Maiko; Ye, Jieru; Lim, Diana; Herrington, C Simon; Iida, Yasushi; Yano, Mitsutake; Yasuda, Masanori; Ngoi, Natalie YL; Wong, SB Justin; Okamoto, Aikou; et al.
Abstract: Little is known about the immune environment of ovarian clear cell carcinoma (OCCC) and its impact on various ethnic backgrounds. The aim of this OCCC immune‐related gene expression signatures (irGES) study was to address the interaction between tumour and immune environment of ethnically‐diverse Asian and Caucasian populations and to identify relevant molecular subsets of biological and clinical importance. Our study included 264 women from three different countries (Singapore, Japan, and the UK) and identified four novel immune subtypes ( PD1‐high, CTLA4‐high, antigen‐presentation, and pro‐angiogenic subtype) with differentially expressed pathways, and gene ontologies using the NanoString nCounter PanCancer Immune Profiling Panel. The PD1‐high and CTLA4‐high subtypes demonstrated significantly higher PD1, PDL1, and CTLA4 expression, and were associated with poorer clinical outcomes. Mismatch repair (MMR) protein expression, assessed by immunohistochemistry, revealed that about 5% of OCCCs had deficient MMR expression. The prevalence was similar across the three countries and appeared to cluster in the CTLA4‐high subtype. Our results suggest that OCCC from women of Asian and Caucasian descent shares significant clinical and molecular similarities. To our knowledge, our study is the first study to include both Asian and Caucasian women with OCCC and helps to shine light on the impact of ethnic differences on the immune microenvironment of OCCC. © 2021 The Authors. The Journal of Pathology published by John Wiley & Sons, Ltd. on behalf of The Pathological Society of Great Britain and Ireland.